Factors Associated with Stunting in Toddlers Aged 24-59 Months - Mulyanti; Marlina (CV. CENDIKIA JENIUS INDONESIA, 2025)
Stunting is a condition where children aged 0-2 years have a height or length that is less than their age. The way to measure this condition is characterized by a height or length that is more than minus two standard deviations of the median of child growth standards from WHO. Stunting is currently still one of the nutritional problems in toddlers in Indonesia that needs to be addressed. This study aims to determine the risk factors that cause stunting such as LBW, Immunization, Infectious Diseases, Exclusive Breastfeeding, Maternal Occupation, Maternal Education and Maternal Knowledge about stunting in toddlers at the UPTD Ibrahim Adjie Health Center, Bandung City in 2024. Data collection was carried out using an interview method using a questionnaire, and nutritional status (H/U) was directly measured in toddlers aged 24-59 years with a sample of 126 respondents. Bivariate analysis used the Chi-Square Test and Fisher's Exact Test. The results showed that there was no relationship between LBW (sig. 0.560), Immunization (0.560), Infectious Diseases (sig. 0.554), and Maternal Education (sig. 1.000) with the incidence of stunting, while Exclusive Breastfeeding (sig. 0.048) and maternal knowledge about stunting (sig. 0.001) had a positive relationship with the incidence of stunting at Ibrahim Adjie Health Center, Bandung City in 2024. The conclusion of this study is that there are 2 factors that are significantly related, namely exclusive breastfeeding and maternal knowledge and 4 factors that are not significant, namely LBW, immunization, infectious diseases and maternal education. It is recommended for mothers who have toddlers to increase their insight into the incidence of stunting in order to prevent stunted child growth and development and provide exclusive breastfeeding.